Household Living Strategy As An Economic Contribution Of Women Vegetable Traders In Traditional Markets - Pitri, Oktia Aninia; Irwan, Irwan; Yuhelna, Yuhelna (Universitas Tanjungpura, 2024)
This research was motivated by the low income of vegetable traders at Bancah Kapeh Market. The income of vegetable traders is not even equal to the monthly household expenses they intend to spend. Household expenses are getting bigger. Likewise, if we trace the 2024 South Solok UMK, the income of vegetable traders is still insufficient and is still below the UMK. This research aims to describe the household characteristics and household livelihood strategies of women vegetable traders as an economic contribution at the Bancah Kapeh Traditional Market, Nagari Lubuk Malako, Sangir Jujuan District, South Solok Regency. The theory used is the livelihood strategy theory put forward by Scoones. The approach used is a qualitative approach with a descriptive type. The data collection technique used was purposive sampling technique. The types of data are primary data and secondary data. Data collection techniques were carried out using document study, observation and in-depth interviews. The analysis used is data analysis developed by Miles and Huberman. Based on the research results, it can be concluded that women vegetable traders continue to fulfill household needs even though their economic conditions can only cover food and clothing. The household livelihood strategy for women vegetable traders is to carry out strategies for engineering sources of livelihood and dual income patterns. A form of livelihood engineering strategy carried out by vegetable traders is by expanding the types of merchandise, adding workers and increasing working hours. Meanwhile, the form of a double livelihood strategy is by utilizing trading skills to meet household needs and utilizing farming skills for household needs. This strategy is carried out by female vegetable traders so that they can increase household income.